The social habitus of Early Years Education: Processes of learning and unlearning | O habitus social da Educação Infantil: processos de aprendizagem e de não aprendizagem - Norman Gabriel (Pontifícia Universidade Católica de Campinas, 2019)
Although Norbert Elias did not explicitly address educational practice or the role of education in society, he was deeply interested in the development of the social learning processes of young children and adults. This paper will begin by looking at Elias's relational perspective on childhood, focusing on the long-term individual civilising processes that young children undergo as they prepare for adulthood in complex societies. It will then focus on two of the major psychoanalytic thinkers of the British object relations school, Donald Winnicott and Wilfred Bion, to understand how these processes of learning are sometimes 'blocked' by teachers in diff erent institutions where it is assumed that pedagogy is predominantly a rational, conscious and deliberate process. I will argue that Elias's distinctive approach to learning can be used to integrate the findings of psychoanalysis, developing a relational sociology of Early Years Education that views schools as anxious institutions where young children have to exercise a more intensive and all-embracing control over their emotions.